Alfabetização científica e o uso de questões sociocientíficas no ensino de Ecologia : uma experiência no contexto de Lagarto – SE - Santos, Tatiane da Silva (2018)
The Scientific Literacy (SL) in the Science curriculum presents a proposal of education focused on the students' citizenship, through the understanding of scientific and technological subjects. Thus, the Socioscientific issues approach (SSI), which considers the dimensions of the STSE (Science, Technology, Society and Environment) approach, the cultural and ethical aspects, the reasoning and the emotional development of the students takes space. In this context, the teaching of Ecology has great relevance due to its complexity and interfaces with other areas of knowledge, coupled with the growing need for greater care with the planet, due to the environmental impacts caused by the anthropic action. The present work has the general objective to analyze the potentialities and limitations of the use of SSI in the teaching of Ecology, in order to contribute to the SL of students of the 6th year of Elementary School of the municipal network of Lagarto, central-southern region of Sergipe. The research is divided in three stages: 1) Investigation of the knowledge of science teachers of the municipal network of teaching of Lagarto, about the SL, the STSE approach and the SSI and how they approach the content of Ecology in their classes; 2) Construction, in a collaborative way with one of these teachers, of a Didactic Sequence (DS) on the theme "use of pesticides in Lagarto"; 3) Application and evaluation of DS. The data collection instrument of the first stage of the research was a questionnaire, answered by 13 of the 22 Science teachers, who demonstrated to have some knowledge about the SL, the STSE approach and the SSI, but in practice, the local reality still seems be addressed in Ecology classes. For DS, five classes were elaborated, with the use of resources and diverse didactic strategies, which made possible the aggrandizement of the teaching and learning process. During the DS application, the participating teacher's commitment was to stimulate the critical thinking of the students, by analyzing the "positive" and negative aspects that involve the use of pesticides. Thus, the students could engage in the discussions, expressing their views on the subject and sharing their experiences. It is concluded, therefore, that the students bring with them a range of knowledge, acquired mainly in their daily living, that need to be worked in the classroom, so that the learning of new contents can have meaning and effectively contribute to the citizen formation of the students. For this to happen, it is necessary that the teacher is concerned with using scientific subjects as a means to understand a social problem, addressing real and current issues.